Effect of fitness on incident diabetes from statin use in primary prevention. Issue 1 (March 2015) - Radford, Nina B.; DeFina, Laura F.; Barlow, Carolyn E.; Kerr, Alice; Chakravorty, Ripa; Khera, Amit; Levine, Benjamin D.
Abstract: Objective: To assess the effect of cardiorespiratory fitness on the association between the initiation of statin therapy and incident diabetes. Patients and methods: In a prospective observational study, we studied 6519 generally healthy men and 2334 women with two preventive health examinations from December 15, 1998 through December 18, 2013 which included measurement of fitness levels, statin therapy, risk factors for diabetes, and incident diabetes. Results: 93 cases of incident diabetes occurred during an average follow-up of 3.0 years. After multivariable adjustment, an increased odds of incident diabetes with statin use was observed in those patients with impaired fasting glucose at baseline (odds ratio [OR]: 2.15, [95% CI:1.26 to 3.67]), but not among individuals with normal glucose levels (OR:1.85, [95% CI: 0.76 to 4.52]). Cardiorespiratory fitness attenuated but did not eliminate the increased risk of incident diabetes with statin use. Conclusion: In a population of relatively healthy patients, statin use was not associated with incident diabetes in patients with normal fasting glucose at baseline. However, it was associated with incident diabetes in those patients with impaired fasting glucose at baseline, though this risk was substantially reduced by increasing fitness. In addition, increasing cardiorespiratory fitness was inversely associated with incident diabetes whether or not a patient was treated with a statin. Highlights: Statin use was not associated with incident diabetes in patients with normal fasting glucose at baseline. Statin use was associated with incident diabetes in patients with IFG, although this risk was reduced by increasing fitness. Higher levels of fitness were inversely associated with incident diabetes whether or not a patient used a statin.